THE EFFECT OF ORGANIZATIONAL CULTURE AND JOB ENVIRONMENT ON EMPLOYEE IN PT. ASTRA INTERNATIONAL TBK. AUTO 2000 BRANCH OF AMPLAS MEDAN - Prayoga, Diki; Firah, Al (Universitas Dharmawangsa Medan, 2023)
ABSTRACTÂ This study aims to determine the effect of organizational culture and work environment on employee performance. PT. Astra International Tbk. Auto 2000 is a Toyota car dealer. The population of this study is 61 employees with a sample according to the slovin formula of 30 employees. The data used is quantitative data derived from primary sources. The data collection technique uses a Likert scale with a regressive line analysis method to provide information to respondents (questionnaire). Based on the statistical results obtained tcount 10.886 > ttable 1.697 it can be concluded that there is a positive influence between organizational variables and work environment variables on employee performance at PT. Astra International Tbk Auto 2000 Sandpaper Branch. Based on the results of the coefficient of determination, the R-Square in the regression is 0.911 (91.1%). In this case, the most significant benefit provided by the organization and the workplace is 91.1%, with the remaining 8.9% coming from other variables that were not considered in the study. PT. Astra Internasional Tbk Auto 2000 Amplas Branch must increase and expand the number of courses aligned with job specifications in order to improve organizational health and workforce productivity.Â Keywords: Organizational Culture, job Environment, Employee Performance